Find the value of $\cos {36^0} - \cos {72^0}$?
Answer
Verified
510.3k+ views
Hint – In this question we have to find the value of the given expression. The basic trigonometric identities like $\cos C - \cos D = 2\sin \left( {\dfrac{{C + D}}{2}} \right)\sin \left( {\dfrac{{D - C}}{2}} \right)$, along with the algebraic identities will help will in simplifying the given expression.
“Complete step-by-step answer:”
Given equation is
$\cos {36^0} - \cos {72^0}$
As we know $\cos C - \cos D = 2\sin \left( {\dfrac{{C + D}}{2}} \right)\sin \left( {\dfrac{{D - C}}{2}} \right)$ so, use this property in above equation we have,
$ \Rightarrow \cos {36^0} - \cos {72^0} = 2\sin \left( {\dfrac{{{{36}^0} + {{72}^0}}}{2}} \right)\sin \left( {\dfrac{{{{72}^0} - {{36}^0}}}{2}} \right)$
Now simplify the above equation we have,
$ \Rightarrow 2\sin \left( {\dfrac{{{{36}^0} + {{72}^0}}}{2}} \right)\sin \left( {\dfrac{{{{72}^0} - {{36}^0}}}{2}} \right) = 2\sin \left( {\dfrac{{{{108}^0}}}{2}} \right)\sin \left( {\dfrac{{{{36}^0}}}{2}} \right) = 2\sin {54^0}\sin {18^0}$
Now we know that $\sin {54^0} = \dfrac{{\sqrt 5 + 1}}{4},{\text{ }}\sin {18^0} = \dfrac{{\sqrt 5 - 1}}{4}$ so, substitute this value in above equation we have,
$ \Rightarrow 2\sin {54^0}\sin {18^0} = 2\left( {\dfrac{{\sqrt 5 + 1}}{4}} \right)\left( {\dfrac{{\sqrt 5 - 1}}{4}} \right)$
Now simplify this using property $\left( {a + b} \right)\left( {a - b} \right) = {a^2} - {b^2}$.
$ \Rightarrow 2\sin {54^0}\sin {18^0} = 2\left( {\dfrac{{\sqrt 5 + 1}}{4}} \right)\left( {\dfrac{{\sqrt 5 - 1}}{4}} \right) = 2\left( {\dfrac{{5 - 1}}{{16}}} \right) = 2\left( {\dfrac{4}{{16}}} \right) = \dfrac{2}{4} = \dfrac{1}{2}$
$ \Rightarrow \cos {36^0} - \cos {72^0} = \dfrac{1}{2}$
Note – Whenever we face such types of questions the key concept is simply to have the gist of basic trigonometric identities, application of these identities combined with algebraic identities helps simplify such trigonometry problems and will get you on the right track to reach the answer.
“Complete step-by-step answer:”
Given equation is
$\cos {36^0} - \cos {72^0}$
As we know $\cos C - \cos D = 2\sin \left( {\dfrac{{C + D}}{2}} \right)\sin \left( {\dfrac{{D - C}}{2}} \right)$ so, use this property in above equation we have,
$ \Rightarrow \cos {36^0} - \cos {72^0} = 2\sin \left( {\dfrac{{{{36}^0} + {{72}^0}}}{2}} \right)\sin \left( {\dfrac{{{{72}^0} - {{36}^0}}}{2}} \right)$
Now simplify the above equation we have,
$ \Rightarrow 2\sin \left( {\dfrac{{{{36}^0} + {{72}^0}}}{2}} \right)\sin \left( {\dfrac{{{{72}^0} - {{36}^0}}}{2}} \right) = 2\sin \left( {\dfrac{{{{108}^0}}}{2}} \right)\sin \left( {\dfrac{{{{36}^0}}}{2}} \right) = 2\sin {54^0}\sin {18^0}$
Now we know that $\sin {54^0} = \dfrac{{\sqrt 5 + 1}}{4},{\text{ }}\sin {18^0} = \dfrac{{\sqrt 5 - 1}}{4}$ so, substitute this value in above equation we have,
$ \Rightarrow 2\sin {54^0}\sin {18^0} = 2\left( {\dfrac{{\sqrt 5 + 1}}{4}} \right)\left( {\dfrac{{\sqrt 5 - 1}}{4}} \right)$
Now simplify this using property $\left( {a + b} \right)\left( {a - b} \right) = {a^2} - {b^2}$.
$ \Rightarrow 2\sin {54^0}\sin {18^0} = 2\left( {\dfrac{{\sqrt 5 + 1}}{4}} \right)\left( {\dfrac{{\sqrt 5 - 1}}{4}} \right) = 2\left( {\dfrac{{5 - 1}}{{16}}} \right) = 2\left( {\dfrac{4}{{16}}} \right) = \dfrac{2}{4} = \dfrac{1}{2}$
$ \Rightarrow \cos {36^0} - \cos {72^0} = \dfrac{1}{2}$
Note – Whenever we face such types of questions the key concept is simply to have the gist of basic trigonometric identities, application of these identities combined with algebraic identities helps simplify such trigonometry problems and will get you on the right track to reach the answer.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE